The CD4+ T-cell subset lacking expression of the CD28 costimulatory molecule is expanded and shows a higher activation state in multiple sclerosis. - Pinto-Medel, María Jesús; García-León, Juan Antonio; Oliver-Martos, Begoña; López-Gómez, Carlos; Luque, Gloria; Arnáiz-Urrutia, Carlos; Órpez, Teresa; Marín-Bañasco, Carmen; Fernández Fernández, Óscar; Leyva-Fernández, Laura (Elsevier, 2012)
Multiple sclerosis (MS) is a chronic debilitating disease, in which T-cells are considered to play a pivotal role. CD28 is the quintessential costimulatory molecule on T-cells and its expression declines progressively with repeated stimulations, leading to the generation of CD28− T-cells. Our aim was to examine whether CD4+CD28- T cells were enriched in MS patients, and characterize the phenotype of this subset in MS patients and healthy controls (HC). All these changes could provide these CD4+CD28- T cell characteristics that might be involved in the pathogenesis of MS, turning this T-cell subset into a potential target for future therapeutic strategies.
Keywords: Esclerosis múltiple; Moleculas de adhesión celular; Células T; CD4+CD28- T cells; NK cell markers; Multiple sclerosis; Activation; Adhesion molecules; Cytotoxic markers